PENGARUH MOTIVASI KERJA, KARAKTERISTIK INDIVIDU DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PT. FIF GROUP CABANG DENPASAR - Putu Intan Puspita Dewi; I Nengah Suardhika; Ni Putu Cempaka Dharmadewi Atmaja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Human resources have a major role in every activity. Without employee support, namely adequate human resources, company activities will not be able to run well. One of the factors that can influence employee performance is work motivation, individual characteristics and organizational climate. This research aims to determine work motivation, individual characteristics and organizational climate on employees performance PT. FIF Group Denpasar Branch. The research objects in this study are work motivation, individual characteristics and organizational climate on employee performance at PT. FIF Group Denpasar Branch. This research used a sample of 60 people. Sampling was carried out using saturated sampling, where the entire population was sampled. The analysis technique used is multiple linear regression analysis. Based on the test results, it can be stated that work motivation has a positive and significant effect on employee performance which can be seen from the sig value of 0.005 < 0.05, so that H0 is rejected and H1 is accepted. Individual characteristics have a positive and significant effect on employee performance which can be seen from the sig value of 0.011 < 0.05, so that H0 is rejected and H2 is accepted. Organizational climate has a positive and significant effect on employee performance which can be seen from the sig value of 0.039 < 0.05, so that H0 is rejected and H3 is accepted.